Exploring the multidimensionality of stature variation in the past through comparisons of archaeological and living populations. Issue 2 (4th June 2014) - Vercellotti, Giuseppe; Piperata, Barbara A.; Agnew, Amanda M.; Wilson, Warren M.; Dufour, Darna L.; Reina, Julio C.; Boano, Rosa; Justus, Hedy M.; Larsen, Clark Spencer; Stout, Sam D.; Sciulli, Paul W.; Reitsema, Laurie J.; et al.
ABSTRACT Adult stature variation is commonly attributed to differential stress‐levels during development. However, due to selective mortality and heterogeneous frailty, a population's tall stature may be more indicative of high selective pressures than of positive life conditions. This article examines stature in a biocultural context and draws parallels between bioarchaeological and living populations to explore the multidimensionality of stature variation in the past. This study investigates: 1) stature differences between archaeological populations exposed to low or high stress (inferred from skeletal indicators); 2) similarities in growth retardation patterns between archaeological and living groups; and 3) the apportionment of variance in growth outcomes at the regional level in archaeological and living populations. Anatomical stature estimates were examined in relation to skeletal stress indicators (cribra orbitalia, porotic hyperostosis, linear enamel hypoplasia) in two medieval bioarchaeological populations. Stature and biocultural information were gathered for comparative living samples from South America. Results indicate 1) significant (P < 0.01) differences in stature between groups exposed to different levels of skeletal stress; 2) greater prevalence of stunting among living groups, with similar patterns in socially stratified archaeological and modern groups; and 3) a degree of regional variance in growth outcomes consistent with that observed for highly selected traits. The relationship between early stress and growth is confounded by several factors—including catch‐up growth, cultural buffering, and social inequality. The interpretations of early life conditions based on the relationship between stress and stature should be advanced with caution. Am J Phys Anthropol 155:229–242, 2014. © 2014 Wiley Periodicals, Inc.